Consecutive Lacunar Strokes Mimicking Brainstem Symptoms in a Patient With Pseudobulbar Palsy - Stocker, Alexander; Struffert, Tobias; Engelhorn, Tobias; Huttner, Hagen (Neurologist, 2015)
The pseudobulbar palsy affects both corticobulbar tracts leading to symptoms of the caudal brain nerves. These bulbar symptoms often may be misinterpreted and lead to a false localization of the ischemic lesion. Here we report on a patient with an acute small lacunar ischemic lesion who presented clinically with severe affection because of an identical old contralateral lesion.The patient presented with sudden onset of dysphagia, anarthria, and glossplegia. The clinical examination was suspicious of a brainstem lesion, however, stroke magnetic resonance imaging revealed a small ischemic lacuna within the right internal capsule. However, because of an old ischemic lesion within the left internal capsule, both corticobulbar tracts were involved and this pseudobulbar palsy was mimicking bulbar brainstem symptoms.Patients who suffer from a pseudobulbar palsy usually have–compared with the rather small lesions within the central nervous system–clinically dramatic presentations and due to bulbar symptoms severe medical secondary complications and social-economic consequences to deal with.
EVALuna2:22360